FACTORS AFFECTING FARMERS IN THE IMPLEMENTATION OF INTEGRATED AGRICULTURAL SYSTEMS IN LANGKAK VILLAGE - Foni Aristia; Devi Agustia (CV. Radja Publika, 2023)
This research aims to determine the factors that influence farmers in implementing an integrated agricultural system in Langkak village, Kuala Coast sub-district, Nagan Raya regency. This research was carried out from October to December 2022. The analytical method used in this research was the logistic regression analysis method and to determine the Y value using dummy variable data, namely 1 = decision to implement integrated agriculture, 0 = decision not to implement integrated agriculture. This research took 30 farmers as samples using a saturated method based on consideration of who took part in the socialization in the 2022 PPK Ormawa program in Langkak village. The data collection techniques used in this research were interviews and observation. Based on data processing, it shows that the variables age, education, land area, length of farming, and income have a big impact on farmers' decisions to implement an integrated farming system. Although simultaneously only the variables age and length of farming have a significant effect, apart from that they do not have a significant effect on farmers' decisions to implement an integrated farming system.